Comparison of Inventory Control with P and Q Model for Ppe At Power Plant Industry (Case Study: Pt. Pjb Ubjom Pltu Indramayu) - Sakanurizal, Ario; Ramdhani, Kustiansyah Reza; Sukmawati, Feby; Nugraha, Indri; Rahmana, Arief (International Journal of Psychosocial Rehabilitation, 2020)
The success of inventory management can be seen from the suitability of the available material and the material used. Research carried out in the power plant company about inventory management of personal protective equipment in the form of masks and gloves. Fluctuating material demand causes overstock and stockout so that operator and maintenance work is constrained. The purpose of this study is to obtain an optimal inventory system policy. Optimal inventory is able to meet user needs and low inventory costs. The method used in this research is P models policy and Q models policy because of the probabilistic demand characteristics. the Q model policy is able to provide greater cost savings than the P model policy. The total savings using the P model policy is Rp. 4,219,970, - and the Q model is Rp. 5,099,733, -.